2021
DOI: 10.1093/asj/sjab202
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Facial Muscle Aging: A Surface Electromyography Study

Abstract: Background Facial aging is a multi-factorial process which involves all tissues of the face including skin, muscles, fat, ligaments, and bone. Whereas robust evidence is available for age-related changes of bone and facial fat, the influence of age on facial muscle activity is poorly understood. Objectives The objective of this study was to investigate the motor unit action potential (MUAP) of facial muscles by utilizing surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“… 17-19 Changes in the facial muscle could also been demonstrated in recently published in vivo electromyography investigations. 7 This could potentially explain the slightly better outcome in females aged 35 to 50 years, as elderly patients might require a higher dosage due to the aforementioned age-dependent processes at the neuromuscular junction. This subanalysis has shown that in the most frequently targeted patient group, facing a certain degree of aging that can be considered mid-aged, 20 U of letibotulinumtoxinA, spread over 5 injection points offers high efficacy with minimal complication rates.…”
Section: Discussionmentioning
confidence: 99%
“… 17-19 Changes in the facial muscle could also been demonstrated in recently published in vivo electromyography investigations. 7 This could potentially explain the slightly better outcome in females aged 35 to 50 years, as elderly patients might require a higher dosage due to the aforementioned age-dependent processes at the neuromuscular junction. This subanalysis has shown that in the most frequently targeted patient group, facing a certain degree of aging that can be considered mid-aged, 20 U of letibotulinumtoxinA, spread over 5 injection points offers high efficacy with minimal complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although the following procedures were not performed in this study, transplanting fat near the malar fat pad is helpful for rejuvenation, as the SMAS thins out after the zygomaticus major muscle is visible. 23,24 In general, Asian patients have larger faces than White patients and have protruding malar eminences. 26 Thus, as the force pulling the flap in front of the tragus is difficult to transmit to the fat in the medial NLF, the same improvement effects are not observed in Asian patients as in White patients.…”
Section: Discussionmentioning
confidence: 99%
“…This facilitates the age-related transition from dynamic to static lines. Thus, providing early injection of neuromodulators may decrease the severity of a patient's static frown lines or even prevent their formation (Cotofana et al, 2021).…”
Section: Suggested Injection Techniquementioning
confidence: 99%